STUDYING THE INTERACTION OF ARTISTIC INTERPRETATION AND AUDIENCE PARTICIPATION IN MUSIC PERFORMANCE - Madaminov Nasimjon Holjorayevich (Journals Park Publishing, 2024)
This study explores the multifaceted nature of musical performance, exploring the complex relationships between technical skill, artistic interpretation, and audience engagement. By comprehensively analyzing these key elements, this study aims to shed light on the mechanisms by which musicians can enhance the quality and impact of their performances. The findings highlight the critical role of technical skill as a foundation for expressive communication, the importance of artistic interpretation in imbuing performances with emotional depth, and the importance of audience engagement in creating a memorable and immersive musical experience.
Keywords: Musical performance, technical skill, artistic interpretation, audience engagement, music, communication.